Barriers to Addressing Adolescent Substance Use: Perceptions of New York School‐Based Health Center Providers. (February 2016) - Harris, Brett; Shaw, Benjamin; Lawson, Hal; Sherman, Barry
ABSTRACT: BACKGROUND: Adolescent substance use is associated with chronic health conditions, accidents, injury, and school‐related problems, including dropping out. Schools have the potential to provide students with substance use prevention and intervention services, albeit with confidentiality challenges. School‐based health centers (SBHCs) provide confidentiality, positioning them as ideal settings to provide substance use prevention and intervention. This study identified program directors' and clinicians' barriers to addressing adolescent substance use in SBHCs. METHODS: Between May and June 2013, an electronic survey was distributed to all 162 New York State SBHC program directors and clinicians serving middle and high school students. RESULTS: The most prevalent perceived barriers to discussing substance use with students were time constraints (43%), the belief that students are not honest about their use (43%), and clinicians' lack of training (28%). Both directors and clinicians identified challenges in getting students to return for additional sessions to address their use, and they also indicated that confidentiality was a treatment referral barrier. CONCLUSIONS: This study identified timely opportunities that may be leveraged and unique challenges that may be overcome with targeted dissemination, training, and technical assistance efforts to enable directors and clinicians to routinely address substance use in SBHCs.